Current Topics in Chikungunya - Rodriguez-Morales, Alfonso J. (IntechOpen, 2016)
Chikungunya, an arbovirus, is a major global threat affecting multiple areas of the world, even Europe, but recently (2014 - 2015) with large epidemics in Latin America, causing an important acute and chronic morbidity with a low, but present, mortality. This book tries to update the significant epidemiological and clinical research in many aspects with a multinational perspective. This book has been organized in two major sections: (I) ''Clinical and Epidemiological Aspects'' and (II) ''Entomology.'' Section I includes topics covering experiences and studies in different countries, including the infection during pregnancy and children, imported cases, ocular manifestations, coinfections, and therapeutics. Section II includes topics on entomological aspects, related to vector control, and new options for biological control of Aedes aegypti.